Serial endometrial thickness and risk of non‐endometrial hormone‐dependent cancers in postmenopausal women in UK Collaborative Trial of Ovarian Cancer Screening. (1st August 2020) - Burnell, M.; Gentry‐Maharaj, A.; Glazer, C.; Karpinskyj, C.; Ryan, A.; Apostolidou, S.; Kalsi, J.; Parmar, M.; Campbell, S.; Jacobs, I.; Menon, U.
ABSTRACT: Objective: Estrogen is a well‐established risk factor for various cancers. It causes endometrial proliferation, which is assessed routinely as endometrial thickness (ET) using transvaginal ultrasound (TVS). Only one previous study, restricted to endometrial and breast cancer, has considered ET and the risk of non‐endometrial cancer. The aim of this study was to explore the association between baseline and serial ET measurements and nine non‐endometrial hormone‐sensitive cancers, in postmenopausal women, using contemporary statistical methodology that attempts to minimize the biases typical of endogenous serial data. Methods: This was a cohort study nested within the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS). In the ultrasound arm of UKCTOCS, 50639 postmenopausal women, aged 50–74, underwent annual TVS examination, of whom 38 105 had a valid ET measurement, no prior hysterectomy and complete covariate data, and were included in this study. All women were followed up through linkage to national cancer registries. The effect of ET on the risk of six estrogen‐dependent cancers (breast, ovarian, colorectal, bladder, lung and pancreatic) was assessed using joint models for longitudinal biomarker and time‐to‐event data, and Cox models were used to assess the association between baseline ET measurement and these six cancers in addition to liver cancer, gastric cancer and non‐Hodgkin's lymphoma (NHL). All models were adjusted for current hormone‐replacement therapy (HRT) use, body mass index, age at last menstrual period, parity and oral contraceptive pill use. Results: The 38 105 included women had a combined total of 267 567 (median, 8; interquartile range, 5–9) valid ET measurements. During a combined total of 407 838 (median, 10.9) years of follow‐up, 1398 breast, 351 endometrial, 381 lung, 495 colorectal, 222 ovarian, 94 pancreatic, 79 bladder, 62 gastric, 38 liver cancers and 52 NHLs were registered. Using joint models, a doubling of ET increased significantly the risk of breast (hazard ratio (HR), 1.21; 95% CI, 1.09–1.36; P = 0.001), ovarian (HR, 1.39; 95% CI, 1.06–1.82; P = 0.018) and lung (HR, 1.25; 95% CI, 1.02–1.54; P = 0.036) cancers. There were no statistically significant associations between ET and the remaining six cancers. Conclusion: Postmenopausal women with high/increasing ET on TVS are at increased risk of breast, ovarian and lung cancer. It is important that clinicians are aware of these risks, as TVS is a common investigation. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.